The Diagnostic Accuracy of the Pitch Glide to Identify Aspiration in Patients with Respiratory Diseases: A Pilot Study - Regan, Julie (My University, 2019)
Introduction: Initial research has been conducted to determine the diagnostic accuracy of the pitch glide during the clinical swallow evaluation to identify aspiration in adults after stroke. Findings suggest that reduced pitch glide can predict aspiration in patients with dysphagia after stroke. This study aimed to identify the diagnostic accuracy of the pitch glide in detecting aspiration, pharyngeal residue and hyolaryngeal excursion during swallowing in adults with respiratory diseases. Material and Methods: 17 adults (9 males and 8 females) with dysphagia who had a background of respiratory diseases (chronic obstructive pulmonary disease = 11; lower respiratory tract infection = 6) were consecutively recruited in an acute hospital setting. Participants completed two pitch glide tasks (/a/ and /i/) immediately before a videofluoroscopic swallowing study (VFSS). Pitch glide recordings were analysed by blinded researchers both acoustically (Praat software) to obtain maximum F0, pitch range and auditory-perceptually using a binary scale (“normal” or “abnormal”). Clinicians blinded to pitch glide ratings rated 5 mL, 10 mL and a sip of liquid swallows during VFSS using the Penetration-Aspiration Scale, Bolus Residue Scale and hyolaryngeal component of the MBS Measurement Tool for Swallow Impairment. Receiver operating characteristic curve, Pearson correlations and independent sample t tests were used to address the research questions. Results: Maximum F0 of sound /a/ had high sensitivity and specificity in identifying aspiration on 10 mL of liquids during VFSS. Both pitch glides (/a/ and /i/) had moderate sensitivity and specificity in predicting aspiration on a sip of liquids. However, auditory-perceptual measures of pitch glide had weak accuracy in identifying people who were aspirating during VFSS. Finally, all pitch glide measures (acoustic and auditory-perceptual) had low accuracy in predicting pharyngeal residue and hyolaryngeal excursion. Conclusion: Based on this initial pilot study, acoustic pitch glide of sound /a/ is an accurate way to predict aspiration on 10 mL of liquids in patients with respiratory diseases. Based on findings from this study, both auditory-perceptual and acoustic analyses of pitch glide could not identify residue and hyolaryngeal excursion.
PUBLISHED
Keywords: Dysphagia; Pitch glide; Diagnostic accuracy; Chronic obstructive pulmonary disease (COPD); Low respiratory tract infections (LRT); Ageing; DYSPHAGIA; Chronic Health Condition; Health